Healthcare Associated Urinary Tract Infections in Medicine Wards - Sawarkar, Dr. Mahendra M.; Sawarkar, Dr. Shushrut Mahendra (International Journal of Innovative Research in Medical Science, 2018)
Health care associated infections (HCAIs) or hospital acquired infections (HAIs) are infections that occur during hospitalization but they are neither present nor incubating before hospital admission. Rapid advancement in medical technology, injudicious use of antibiotics and better adaptation of organisms to the hospital environment contribute to increase in HAIs. Healthcare-associated urinary tract infections (HAUTIs) are frequently increasing and largely preventable infections affecting the provision of healthcare. Material and Methods: Cases included patients admitted in wards of medicine department. Inclusion criteria: included patients are who were admitted for at least for past 48 hours, or readmitted in less than 14 days after their discharge from hospital. Confirmed HAI was defined as clinical signs and microbiological confirmation; potential HAI: association of several clinical signs with no microbiological confirmation; less potential HAI: a single clinical sign with no microbiological confirmation; no potential HAI: no clinical signs. Sociodemographic data from all the included patients was confirmed from medical records. All clinical history was obtained from the patients. Signs of HAI were observed and recorded. Results: A total of 528 patients were included in the studies who were admitted in the medicine wards. Of the 528 patients 276 (52.3%) were male and 252 (47.7%) were female. 87 patients were diagnosed as HAI patients of which 37 (42.5%) were male and 50 (57.5%) were female. Mean age of HAI patients was 51.3 ± 15.74 while total mean of age was 44.2 ± 24.77. Mean age of male with HAI 49.5 ± 11.99 and female was 52.4 ± 13.47. Of the total 10 culture positive patients with HAI Escherichia coli was isolated in 3 cases, Klebsiella pneumonia, Pseudomonas aeruginosa and Staphylococcus aureus were isolated in 2 cases each. While Acinetobacter spp. was isolated in 1 case. Conclusion: This study shows the prevalence of HAI in Urinary tract infection as 15.3% which was quite high but there is no mortality due to UTI and HAI. Periodic active surveillance over a longer period is required to evaluate the efficacy of preventive measures.